Mycotoxins and Crop Yield in Maize as Affected by Irrigation Management and Tillage Practices - Marta Herrera; José Cavero; Samuel Franco-Luesma; Jorge Álvaro-Fuentes; Agustín Ariño; Susana Lorán (Agronomy, 2023)
In addition to the weather conditions, agronomic practices can have a major influence on maize crop yield and contamination with mycotoxins. In this work, the effect of different irrigation systems (flood vs. sprinkler irrigation), sprinkler irrigation management (low vs. high frequency, daytime vs. nighttime irrigation) and tillage practices (conventional tillage, no tillage with or without crop stover) on crop yield and the contamination with aflatoxins (AFs), fumonisins (FUM) and deoxynivalenol (DON) were evaluated in the maize grain from two experimental maize fields. No aflatoxins were detected in any of the samples analyzed. DON and FUM levels were significantly higher when the sprinkler irrigation was performed at nighttime (0.54 and 1.21 mg kg−1, respectively) as compared to daytime (0.38 and 0.45 mg kg−1). Likewise, DON and FUM were greater when irrigation frequency was low (0.61 and 1.09 mg kg−1, respectively) in comparison with high frequency (0.30 and 0.57 mg kg−1). DON concentrations were significantly higher in fields with sprinkler irrigation (0.53 mg kg−1) as compared to flood irrigation (0.19 mg kg−1), while the levels of FUM were very similar regardless of the maize irrigation system. Mycotoxin concentrations were not affected by the different soil tillage practices. This highlights the importance of implementing crop management practices to minimize the risk of mycotoxin contamination in maize.